2018
DOI: 10.1183/13993003.00882-2018
|View full text |Cite
|
Sign up to set email alerts
|

Adverse respiratory effects of opioids for chronic breathlessness: to what extent can we learn lessons from chronic pain?

Abstract: We would like to thank K.T.S. Pattinson and colleagues for their interest in our review and their comprehensive comments [1]. We agree that the quality of the included studies was low, and the studies were small and not designed to examine the safety of opioids, as stated in our discussion [2]. Indeed, respiratory depression was not included as an outcome in over half of the studies. Of note, in the 25 studies that did include the outcome, only 11 stated a definition. Therefore, we recommended in our review to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…However, a dose titration study of extended release morphine for breathlessness showed that over half of responders did so by 10 mg per 24 h and over 90% by 20 mg per 24 h [24]; doses not associated with excess mortality or hospital admission in 4 years' follow-up of people with severe COPD [25]. These are doses markedly lower than those associated with psychological dependence and misuse; issues in relation to opioids for pain should not be automatically assumed for breathlessness [26]. The misuse potential is lower with extended release preparations compared with immediate release [27] and for morphine compared with other oral opioids [28].…”
mentioning
confidence: 99%
“…However, a dose titration study of extended release morphine for breathlessness showed that over half of responders did so by 10 mg per 24 h and over 90% by 20 mg per 24 h [24]; doses not associated with excess mortality or hospital admission in 4 years' follow-up of people with severe COPD [25]. These are doses markedly lower than those associated with psychological dependence and misuse; issues in relation to opioids for pain should not be automatically assumed for breathlessness [26]. The misuse potential is lower with extended release preparations compared with immediate release [27] and for morphine compared with other oral opioids [28].…”
mentioning
confidence: 99%